Multi-dimensional poverty index and tackling interlocking deprivations in the Arab States - Abdel-Hameed Nawar (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
Research into multidimensional poverty has gathered momentum in the last half decade, most notably in the aftermath of the global food and financial crises of 2007-2008. It has gained further momentum since the UNDP-OPHI launched the 2010 Human Development Report (HDR) and more recently as part of the continuing debate on the post-2015 global development agenda. The availability of very large and rich datasets on households and individuals from micro surveys and the advances in survey data analysis have transformed the research. Not only does this raise new policy questions, but it also suggests new policy instruments. Multidimensional poverty theories have been vigorously advocated by some of the most thoughtful and hard-working economists. The Alkire-Foster Multidimensional Poverty Index (MPI) measures overlapping multiple deprivations that people face simultaneously. It is compatible with the Millennium Development Goals and has the advantage that it distils this of multiple indicators into a single score. While the standardised global MPI model allows for international comparisons to be made for different countries, numerous caveats exist when using it nationally 'as is' Individual countries can refine the global MPI model to make it more applicable to their own conditions by expanding the scope for incorporating national- or subnational-specific dimensions, indicators, weights and cut-offs. This paper analyses the 2013 round of the multidimensional poverty and inequality results for Arab States at the national and subnational levels using the results from the OPHI's Alkire-Foster standardised global MPI model. It also explores how some countries in the Arab region can use the MPI as a tool to develop targeted policies aimed at tackling the 'hard core of poverty' at a national and subnational level.
Keywords: I3; I32; D63; O1; 330; Multidimensional Poverty; Inequality; MDGs; Arab States